THE CONTRIBUTION OF ELT IN ASEAN’S COMMUNITY: Spreading the Language of Trade, Finance, Science and Technology - Nursyamsi. H Nursyamsi. H (Universitas Lancang Kuning, 2014)
The aims of this paper is to share a “thought” of English as a multicultural language in Asia based on thefact that English stays as an indispensable language for intranational and/or international communication especially in Southeast Asia. The papers also discussed the contributions of ELT in promoting English as the language of trade, finance and technology in ASEAN region. The significant status of English in Southeast Asian countries since few decades recognized as the second language, or the chief foreign language. This paper also discussed the prediction of the future of English in ASEAN. As well as discussing English as an indisputable lingua franca for regional cooperation in the ASEAN (Association of Southeast Asian Nations) organization comprising ten states.